Feasibility of a Hyperthermic Intraperitoneal Chemotherapy (HIPEC) Program for Gastrointestinal and Gynecological Cancer Care in Newfoundland and Labrador - Kala Hickey; Stephanie Gill; Zoë Breen; Kaitlyn Harding; Hannah Yaremko; Alex Mathieson; Patti Power; David Pace; Joannie Neveu (Onco)
Peritoneal carcinomatosis is a common presentation found in advanced-stage gastrointestinal (GI) and gynecological cancers. Combined cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) is associated with significant survival benefits for select patients. CRS/HIPEC is not currently provided in Newfoundland and Labrador (NL). The Canadian HIPEC Collaborative Group recommends that centres complete a minimum of one case monthly to maintain competency and achieve good outcomes. Thus, we aimed to demonstrate that the annual patient volume in NL justifies the feasibility of implementing a combined surgical and gynecological oncology CRS/HIPEC program. Methods: A retrospective chart review of the NL Cancer Care Registry identified patients with stage IV colorectal, appendiceal, or gastric cancer and stage III to IV epithelial ovarian cancer over a 1-year period (1 January 2020–31 December 2020) to identify the number of patients meeting the criteria for CRS/HIPEC and/or those referred out of province to receive the treatment. The results are presented as proportions and percentages. Results: Thirty-one patients were eligible to receive CRS/HIPEC during the study period (11 GI, 20 gynecological). Of the GI patients, 63% were referred out of province for the procedure. Gynecological patients underwent CRS and systemic therapy +/− outpatient intraperitoneal chemotherapy in NL. Conclusions: Allowing patients to receive this standard of care treatment near home reduces financial, social, and emotional stressors. Our results confirm a sufficient patient volume to support a combined CRS/HIPEC program in NL. The implementation of this program will require multidisciplinary collaboration, specialized training, equipment, and protocol development.